2009
DOI: 10.1097/phm.0b013e31818e6140
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work After Spinal Cord Injury

Abstract: RTW was successful in 33% of the subjects. Wheelchair capacity was independently related to RTW. Therefore, it is recommended to train wheelchair capacity in the context of RTW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, from the clinical perspective, it might be considered irrelevant whether better exercise capacity contributes to better wheelchair skills, better wheelchair skills contribute to better exercise capacity, both or neither. Clinicians need not prioritize one form of intervention over the other, because both are known to be beneficial [1][2][3][4][5][6][7][8][9][10]. Presumably the two interventions complement one another and can be utilized as related elements in a multimodal rehabilitation strategy, as Gant et al have suggested [54].…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from the clinical perspective, it might be considered irrelevant whether better exercise capacity contributes to better wheelchair skills, better wheelchair skills contribute to better exercise capacity, both or neither. Clinicians need not prioritize one form of intervention over the other, because both are known to be beneficial [1][2][3][4][5][6][7][8][9][10]. Presumably the two interventions complement one another and can be utilized as related elements in a multimodal rehabilitation strategy, as Gant et al have suggested [54].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Improving wheelchair users' wheelchair handling skills not only improves their mobility but can also enhance their participation [1][2][3][4][5][6]. Improving wheelchair users' exercise capacity can enhance their health [7,8] and quality of life [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances in the conceptualisation of return to work, most studies continue to employ single metrics as the primary indicator of success in returning to work. Metrics commonly reported in the literature include duration of work disability (Blonk et al 2006), the number of hours of paid work per week (van Velzen et al 2009a), return to full duty work (Marras et al 2007;Holtslag et al 2007) or simply whether the individual has returned to work at a predetermined time period (Casso et al 2004;Gabbe et al 2007). Such uni-dimensional evaluations of return to work do not provide a comprehensive evaluation of an individual's vocational status.…”
mentioning
confidence: 99%
“…Similarly, Foreman et al, 22 in a study of the demographic and psychological factors that may influence sport participation, found no association between sports and employment status; however, the study did show that those with higher income were more likely to participate. Although several studies have linked fitness-related parameters to employment such as wheelchair mobility, body composition, power output, functional independence (as measured by the Functional Independence Measure), number of medical complications, and perceived exertion, 2325 few have directly investigated the association between organized sports and employment.…”
mentioning
confidence: 99%